Perlindungan Konsumen dalam Transaksi Jual Beli Emas Berbasis Aplikasi: Perspektif Hukum Ekonomi Syariah - Fauzan Fauzan (Al-Musthofa: Journal of Sharia Economics, 2026)
This study aims to analyze consumer protection in digital application-based gold buying and selling transactions from the perspective of sharia economic law. The rapid advancement of financial technology (fintech) has accelerated the adoption of digital gold trading platforms in Indonesia, making gold investment accessible to a broader segment of the population, including millennials and Generation Z. However, this convenience brings with it complex legal and sharia compliance challenges that have not been adequately addressed by existing regulatory frameworks. Issues such as the absence of physical handover (qabdh haqiqi), ambiguity in the legal status of digital gold balances, potential gharar (uncertainty) and riba al-nasi’ah in deferred transactions, and the lack of transparent akad (contract) information pose significant risks to consumers. This research employs a qualitative method with a normative juridical approach, examining primary legal sources including the Quran, hadith, classical fiqh literature, DSN-MUI fatwas, and applicable positive laws, supplemented by empirical data from documentation analysis and literature review of existing studies on digital gold platforms. The findings reveal three critical gaps: (1) al-tsubut (legal certainty) is undermined by unclear ownership status of digital gold balances; (2) ‘adl (justice) is compromised by unilateral contract clauses and opaque fee structures; and (3) shidq (transparency) is lacking due to insufficient akad disclosure and limited consumer financial literacy. This study recommends regulatory harmonization between OJK, Bappebti, and DSN-MUI, mandatory sharia certification for digital gold platforms, and structured consumer education programs as essential steps toward strengthening sharia-compliant consumer protection in Indonesia’s growing digital gold market.